Implications of Uncertainty in the Status of Palilah Griya Pasiten Letter Holders in the Baluwarti Area - Dipta, Pramandini Amara; Jamin, Mohammad; Najicha, Fatma Ulfatun (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study analyzes the legal status of Palilah Griya Pasiten Letter in the Baluwarti area of Surakarta within Indonesia's national agrarian law framework. Surat Palilah, issued by the Surakarta Palace as an authorization to occupy and use palace land, has no clear position under the Basic Agrarian Law (UUPA), creating legal uncertainty, particularly in land registration and certification. This research applies normative legal methods, drawing on statutory, historical, and conceptual approaches, and is supported by empirical interviews as complementary data. The study examines the legal standing of Palilah land, available forms of legal protection, and obstacles in the registration process. The findings show that Palilah land cannot be certified as ownership or building use rights and may only be recognized as a Right of Use with Palace approval. The study contributes to agrarian law scholarship by clarifying the normative gap between traditional palace land governance and the national land law system and by providing a conceptual basis for strengthening legal protection within a pluralistic agrarian framework.